Validation of Reference Genes for Quantitative Real-Time PCR Normalization in Ananas comosus var. bracteatus During Chimeric Leaf Development and Response to Hormone Stimuli - Mao, Meiqin; Xue, Yanbin; He, Yehua; Zhou, Xuzixing; Hu, Hao; Liu, Jiawen; Feng, Lijun; Yang, Wei; Luo, Jiaheng; Zhang, Huiling; Li, Xi; Ma, Jun (Frontiers in Genetics, 2021)
Reverse transcription quantitative real-time PCR (RT-qPCR) is a common way to study gene regulation at transcriptional level due to its sensibility and specificity, but it needs appropriate reference genes to normalize data. Ananas comosus var. bracteatus, with white-green chimeric leaves, is an important pantropical ornamental plant. Up to date, no reference genes have been evaluated in Ananas comosus var. bracteatus. In this work, we used five common statistics tools (geNorm, NormFinder, BestKeeper, ΔCt method, RefFinder) to evaluate 10 candidate reference genes. The results showed that Unigene.16454 and Unigene.16459 were the optimal reference genes for different tissues, Unigene.16454 and zinc finger ran-binding domain-containing protein 2 (ZRANB2) for chimeric leaf at different developmental stages, isocitrate dehydrogenase [NADP] (IDH) and triacylglycerol lipase SDP1-like (SDP) for seedlings under different hormone treatments. The comprehensive results showed IDH, pentatricopeptide repeat-containing protein (PPRC), Unigene.16454 and caffeoyl-CoA O methyltransferase 5-like (CCOAOMT) are the top-ranked stable genes across all the samples. The stability of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was the least during all experiments. Furthermore, the reliability of recommended reference gene was validated by the detection of porphobilinogen deaminase (HEMC) expression levels in chimeric leaves. Overall, this study provides appropriate reference genes under three specific experimental conditions, and will useful for future research on spatial and temporal regulation of gene expression and multiple hormones regulation pathways in Ananas comosus var. bracteatus.